The Influence Of Level Of Disclosure On Brand Evaluation And Brand Recall With Psychological Trait Reactance And Program Involvement As Moderator Variables And Program Liking As Intervening Variables (Study On Subway Placement Products In The Korea Drama - Ifada, Shafa Radisya Aulia; Widodo, Teguh (UNIVERSITAS PAKUAN, 2024)
This research is motivated by product placement, which serves as an alternative to traditional advertising usually broadcasted on mass media and frequently used in Korean dramas. Given the popularity of Korean dramas among international audiences, global brands have sought to participate in such product placement activities. However, there are instances where viewers complain about excessive and unreasonable product placements that disrupt their engagement due to their frequent appearances. The purpose of this study is to examine the impact of level of disclosure (LoD) on brand recall (BR) and brand evaluation (BE), while considering the moderating effects of psychological trait reactance (PTA) and program involvement (PI), with program liking (PL) acting as a mediating variable. The study focuses on subway product placement in the Korean drama